Industry Switching in Developing Countries - Newman, Carol (Oxford University Press on behalf of the World Bank, 2014)
Firm turnover (i.e., firm entry and exit) is a well-recognized source of sector-level productivity growth. In contrast, the role and importance of firms that switch activities from one sector to another is not well understood. Firm switchers are likely to be unique, differing from both newly established entrants and exiting firms that are closing down operations. In this study, we develop an empirical model that examines switching behavior using data from Vietnamese manufacturing firms during the 2001–2008 period. The diagnostic shows that switching firms exhibit different characteristics and behavior than do entry and exit firms. Switchers tend to be labor intensive and to seek competitive opportunities in labor-intensive sectors in response to changes in market environments. Moreover, resource reallocation resulting from switching forms an important component of productivity growth. The topic of switching merits attention in the future design of firm surveys across developing countries and in associated analytical studies.